Answer:
13.42
Step-by-step explanation:
9514 1404 393
Answer:
A. f^-1(x) = x³ -12
Step-by-step explanation:
The inverse function can be found by solving ...
x = f(y)
x = ∛(y +12) . . . . . use the definition of f(x)
x³ = y +12 . . . . . . . cube both sides to eliminate the radical
x³ -12 = y . . . . . . . add -12 to isolate the y-variable
f^-1(x) = x³ -12 . . . matches choice A
Step-by-step explanation:
please mark me as brainlest
Answer:
10
Step-by-step explanation:
4 x 10 = 40
40 + 12 = 52
I'm sorry I don't know what this is can you explain it sike